Izit? Hoe lyk hulle? Kom ons Ç‚Xoa "“ A South African Khoe-San narrative - Gabie, Sharon (Rhodes University, Faculty of Humanities, Department of Anthropology)
The foundation of the South African narrative is framed by identity politics; a politics instituted at the intersection of race and class to exclude all people considered non-White concerning the socioeconomic and political landscape of the country. The preamble of the Freedom Charter signed in 1955 declared that the country belongs to all who live in it: Black and White people. The dominant constructivist narratives of addressing the racial dichotomy obliterate the injustice suffered by the Khoe-San people whose identity was overshadowed under the homogeneous term, Coloured people. Following the first democratic elections, at the negotiations of the Convention for a Democratic South Africa (CODESA) in 1996, Khoe-San people were once again excluded and played no significant role in deciding the future of the new South Africa. The epistemic injustice suffered by the Khoe-San people, the loss of land, language, and cultural heritage were glanced over in the new democratic dispensation. In this thesis, I hone into the identity politics and identity formation of the Khoe-San people, after 1994. The self-identifying Khoe-San people became visible to the democratic state through various forms of activism and networking across provinces foregrounding the concept of indigeneity to address issues of exclusion and marginalisation. The phenomenon of indigeneity, bestowed on Khoe-San people by the United Nations Declaration on the Rights of Indigenous People (UNDRIP) created a path for the Khoe-San people to be in conversation with state organs to address their plight of the loss of land linked to identity, language, culture, heritage, and other social ills experienced in their communities. The thesis illustrates the vagueness of Coloured identity under the Apartheid state, and the preconceived narrative that Coloured people were a privileged group; precludes and obliterates the epistemic injustice suffered by Khoe-San people. The transnational conceptualisation and global politics of indigenous peoples; the particularity of indigeneity in relation to First Nation Status, in the South African context, destabilises identity politics and the four-tier racial categorisation system used by the Apartheid state carried through by the national government under democracy. The conceptualisation of this global discourse on indigeneity brought a new consciousness in sections of the Coloured community where self-identifying Khoe-San people question their place in the democratic dispensation.
Keywords: San (African people); Khoikhoi (African people); Identity politics; Self-perception; Convention for a Democratic -- South Africa; Free, prior, and informed consent (Indigenous rights); Epistemic injustice